2005
DOI: 10.1128/iai.73.5.3104-3114.2005
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors Specifically Targeting Type III Secretion

Abstract: The type III secretion (TTS) system is used by several animal and plant pathogens to deliver effector proteins into the cytosol of the eukaryotic target cell as a strategy to evade the defense reactions elicited by the infected organism. The fact that these systems are highly homologous implies that novel antibacterial agents that chemically attenuate the pathogens via a specific interaction with the type III secretion mechanism can be identified. Type III secretion (TTS) constitutes a common virulence system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
223
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(234 citation statements)
references
References 52 publications
9
223
0
2
Order By: Relevance
“…A class of acylated hydrazones was recently identified that inhibited TTS of Y. pseudotuberculosis without affecting the in vitro growth rate (2,3). The same class of compounds has also been shown to inhibit TTS of Pseudomonas aeruginosa as well as S. typhimurium (unpublished data), suggesting that these compounds target the secretory apparatus itself rather than individual effector molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A class of acylated hydrazones was recently identified that inhibited TTS of Y. pseudotuberculosis without affecting the in vitro growth rate (2,3). The same class of compounds has also been shown to inhibit TTS of Pseudomonas aeruginosa as well as S. typhimurium (unpublished data), suggesting that these compounds target the secretory apparatus itself rather than individual effector molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Caminosides, unique glycolipids, were isolated from the marine sponge Caminus sphaeroconia in a screen system in which Esp proteins, secreted from EPEC, were detected by SDS-polyacrylamide gel electrophoresis (SDS-PAGE). 9 Salicylidene acylhydrazide compounds inhibit the functioning of T3SS in Yersinia, 10,11 Chlamydia, 12-14 Shigella, 15 EHEC 16 and Salmonella. 17,18 Furthermore, 2-imino-5-arylidene thiazolidinone inhibits T3SS function at the transcriptional level in Salmonella and in a plant pathogen, Pseudomonas syringae.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have laid the groundwork for a new class of antibiotics that target regulation of these virulence mechanisms. Several recent reports have described the identification of many such drugs, including inhibitors of type III secretion, quorum sensing, and toxin activity (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%